Perbandingan Kemampuan Multirepresentasi Fisika Ditinjau dari Kemampuan Berpikir Konkret dan Formal Siswa - Intan Puspita Sari; Chandra Ertikanto; Feriansyah Sesunan (Jurnal Pembelajaran Fisika, 2017)
This research aimed to determine the differences of multirepresentation skills in physics at three levels (symbolic, submicroscopic, and macroscopic) between students with concrete thinking skill and students with formal thinking skill. The population in this study was all students of class X IPA SMAN 1 Terbanggi Besar, while the selected sample with purposive sampling technique was the students of class X IPA 1. Data of students concrete and formal thinking skill was obtained from the Science Cognitive Development Test (SCDT) score, while data of students multirepresentation skills was known through the multirepresentation skills test scores. Based on the results of mann whitney and independent sample t test can be concluded that: (1) There is a difference in the multirepresentation skills, submicroscopic representation skill, and symbolic representation skill between students with concrete thinking skill and students with formal thinking skill. (2) There is no difference in the macroscopic representation skill between students with concrete thinking skill and students with formal thinking skill. Penelitian ini bertujuan untuk mengetahui perbedaan kemampuan multirepresentasi fisika pada tiga level (simbolik, submikroskopik, dan makroskopik) antara siswa yang berpikir konkret dan siswa yang berpikir formal. Populasi penelitian ini adalah seluruh siswa kelas X IPA SMAN 1 Terbanggi Besar, sedangkan sampel dipilih dengan teknik purposive sampling yaitu siswa kelas X IPA 1. Data kemampuan berpikir konkret dan formal siswa diperoleh dari skor Science Cognitive Development Test (SCDT) sedangkan data kemampuan multirepresentasi siswa diketahui melalui skor tes kemampuan multirepresentasi. Berdasarkan hasil uji mann whitney dan independent sample t test dapat disimpulkan bahwa: (1) Terdapat perbedaan kemampuan multirepresentasi, representasi submikroskopik, dan representasi simbolik antara siswa yang berpikir konkret dan siswa yang berpikir formal (2) Tidak terdapat perbedaan kemampuan representasi makroskopik antara siswa yang berpikir konkret dan siswa yang berpikir formal.Kata Kunci:Formal, Konkret, Multirepresentasi, SCDT